Ratio legis est anima legis and the need to exist and strengthen the state conservation service in Poland - Dobosz, Piotr (Protection of Cultural Heritage, 2016)
This article focuses on the Latin legal maxim read as „ratio legis est anima legis.” It needs to be emphasised that, unless they are well-considered, no approval will be granted to acts which are invalid from legal and formal perspective or under which legally incorrect substantive solutions are to come into force. The author of this article claims that Polish central government may prove useful in the field of protecting historic monuments and sites. Furthermore, the article also explores experiences through which the German government went in the areas pertaining to constitutional law and organisation of German (federal and lance) historic preservation administration. In the conclusion, the author summarizes his deliberations on the Polish model of administrative bodies responsible for conservation and protection of historic monuments and sites.